Diastolic Dysfunction in Neonates With Hypoxic-Ischemic Encephalopathy During Therapeutic Hypothermia: A Tissue Doppler Study - Rodriguez, Maria Jose; Martinez-Orgado, Jose; Corredera, Araceli; Serrano, Irene; Arruza, Luis (Frontiers in Pediatrics, 2022)
Diastolic dysfunction often complicates myocardial ischemia with increased mortality rates. However, little is known about diastolic function after perinatal asphyxia in neonates with hypoxic-ischemic encephalopathy (HIE) during therapeutic hypothermia (TH) and rewarming. Aims: To assess diastolic function with tissue Doppler imaging (TDI) in neonates with moderate-severe HIE during TH and rewarming. Methods: newborns >36 weeks’ gestation with moderate-severe HIE treated with TH were evaluated with targeted neonatal echocardiography (TNE) including TDI, within 24 hours of starting TH (T1), at 48-72 hours of treatment (T2) and after rewarming (T3). These retrospective data were collected and compared with a control group of healthy babies >36 weeks’ gestation prospectively evaluated following the same protocol. Results: 21 HIE+TH patients and 15 controls were included in the study. Myocardial relaxation before the onset of biventricular filling was prolonged in the HIE+TH group during TH with significantly longer isovolumic relaxation time (IVRT’) in the left ventricle (LV), the septum and the right ventricle (RV). This was associated with slower RV early diastolic velocity (e’) and prolonged filling on T1. Total isovolumic time (isovolumic contraction time [IVCT’] + IVRT’) and myocardial performance index (MPI’) were globally increased in asphyxiated neonates. All these differences persisted after correction for heart rate (HR) and normalized after rewarming. TDI parameters assessing late diastole (a’ velocity or e’/a’ and E/e’ ratios) did not differ between groups. Conclusion: TDI evaluation in our study demonstrated a pattern of early diastolic dysfunction during TH that normalized after rewarming, whereas late diastole seemed to be preserved. Our data also suggests a possible involvement of impaired twist/untwist motion and dyssynchrony. More studies are needed to investigate the impact and therapeutic implication of diastolic dysfunction in these babies, as well as to clarify the role of TH in these findings.